A new highway cost allocation framework in the day of connected and autonomous vehicles - Bismark Agbelie (Transportation Research Interdisciplinary Perspectives, 2024)
The objectives of the present study are to explore potential changes expected in highway infrastructure expenditures and revenues, and develop a robust framework that will facilitate highway cost allocation when connected and autonomous vehicles (CAVs) are in operation. The scope of this study covered both federal and state expenditures and revenue sources. The highway cost allocation elements covered in the paper include vehicle miles of travel, highway expenditures highway revenues, and equity analysis. In the day of CAVs, significant changes are expected in all these elements, and these changes are incorporated into the proposed highway cost allocation framework. Pavement-related expenditures would increase due to the addition of CAV-related infrastructure integrated into the pavement infrastructure to ensure it is an intelligent pavement. Bridge-related expenditures are expected to increase due to the infrastructure technologies on the bridges making them smart bridges, and the design loads of these bridges may have to be increased due to potential platooning on long span bridges. It is expected that many of the CAVs on the road will be electric vehicles. All these changes are incorporated into the proposed highway cost allocation framework.